Blackness, Afro-descendants and miscegenation: implications of the ethnic self-identification question of the 2017 National Census for the Afro-Peruvian population - Higashi Suárez, Ana Sofía (2022)
Policies and strategies for the recognition of ethnic identities in Latin American countries are increasingly constant and massive. Among these are self-identification questions in population management instruments, for example, those that include variables such as ethnic identities and the categories used to name them. Within this context, the 2017 Peruvian census is recognized as one of the first and main massive tools used to quantitatively measure the number of individuals who identified with certain ethnic categories and analyze their specific living conditions. The question on ethnic self-identification, however, presented biases, confusion, and concerns. The case of Afro-descendant identities was surrounded by debates and controversies, which led to both personal and public reflections. In this essay, through a review of specialized bibliography, the question of ethnic self-identification in Peru is analyzed, taking into account the construction of Peru as “mestizo”, the context of reethnization in Latin America and the particular construction of Afro-Peruvian identities. Aspects such as social movements, the idea of miscegenation, the recognition of Afro-descendant ancestry and the racial influence on Afro identities finally shaped the responses of Afro-descendant populations that could be obtained. These last factors have meant that the results around the ethnic self-identification questions are not so easy to break down, due to the contradictions and ambiguities that exist behind the ethnic identities themselves.